Identification of phosphorylated residues that affect the activity of the mitotic kinase Aurora-A - Littlepage, Laurie E. (National Academy of Sciences, 2002)
The activity of the kinase Aurora-A (Aur-A) peaks during mitosis and depends on phosphorylation by one or more unknown kinases. Mitotic phosphorylation sites were mapped by mass spec sequencing of recombinant Aur-A protein that had been activated by incubation in extracts of metaphase-arrested Xenopus eggs. Three sites were identified: serine 53 (Ser-53), threonine 295 (Thr-295), and serine 349 (Ser-349), which are equivalent to Ser-51, Thr-288, and Ser-342, respectively, in human Aur-A. To ask how phosphorylation of these residues might affect kinase activity, each was mutated to either alanine or aspartic acid, and the recombinant proteins were then tested for their ability to be activated by M phase extract. Mutation of Thr-295, which resides in the activation loop of the kinase, to either alanine or aspartic acid abolished activity. The S349A mutant had slightly reduced activity, indicating that phosphorylation is not required for activity. The S349D mutation completely blocked activation, suggesting that Ser-349 is important for either the structure or regulation of Aur-A. Finally, like human Aur-A, overexpression of Xenopus Aur-A transformed NIH 3T3 cells and led to tumors in nude mice. These results provide further evidence that Xenopus Aur-A is a functional ortholog of human Aur-A and, along with the recently described crystal structure of human Aur-A, should help in future studies of the mechanisms that regulate Aur-A activity during mitotic progression.